PROBLEMS OF THE INWARD PROCESSING CUSTOMS REGIME AND WAYS TO ELIMINATE THEM - Abdullaev Shakhzodbek (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article examines the economic, organizational, and legal challenges encountered under the inward processing customs regime and proposes ways to address them. It also analyzes international practices and provides recommendations adapted to the context of Uzbekistan.